La omnicanalidad en el e-commerce (2022)
The omnichannel model, which is characterized in that the user is placed at the center of the relationship with the company and it proposes it and / or the sale of products from the experience, and not from each channel in particular. Taken to the extreme. a user's shopping experience should be able to be the same at any brand touchpoint. Although it is easy to say and very complicated to do, because the word itself implies that the companies that try it are, deep down thinking, in channels. (Ricart, 2019, Marketing section). The lack of omnicanality of ecommerce is a situation that over time has been influenced by multiple factors, such as competition; faced with this, the reliability they offer, the prices and budget of the client, the commercial strategies, the security, and others; consumers, exposed to so many stimuli in physical stores, will repeatedly seek to avoid the saturation of these places and eliminate those that are not necessary for the purpose of their purchase. More and more consumers do not have time to buy, so they seek to buy quickly and easily, so the purchase process is intensified as a discard process. Therefore, technology plays a very important role. The purpose of this research is to analyze the implementation of omnichannel as one of the main marketing strategies that ensures that companies offer a quality service.